1971
DOI: 10.1159/000211810
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on Tissue Protein Synthesis

Abstract: Currently available data on the effect of age in tissue protein synthesis and turnover are reviewed and experimental evidence is presented on age changes in amino acid incorporation by rat liver purified microsomes. It has been observed that the purification of ‘crude’ microsomal preparations from contaminating lysosomes by density gradient centrifugation is accompanied by an increase in amino acid incorporatmg activity of the microsomal preparations, no matter whether these are prepared from young or from old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1978
1978
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Kurtz ( I 975) found an age-related decline in polyphenylalanine synthesis with liver microsomes from C57BL/6J mice of I , 2 , 14, 27, and 31 months of age. Hrachovec (1971) observed an age-associated 5 0 0 /~ decrease in liver protein synthesis using microsomes isolated from male albino rats of ages 2-3, 7-1 I , and 19-25 months. Other workers also found a decline in protein synthesis with liver microsomes isolated from adult and senescent rats (Hrachovec, 1969;Buetow & Gandhi, 1973;Comolli, 1973;Junghahn & Bielka, 1974;Hellthaler et al, 1976;Buetow et al, 1977).…”
Section: Rationale For the Study Of Protein Metabolism During Agingmentioning
confidence: 87%
See 2 more Smart Citations
“…Kurtz ( I 975) found an age-related decline in polyphenylalanine synthesis with liver microsomes from C57BL/6J mice of I , 2 , 14, 27, and 31 months of age. Hrachovec (1971) observed an age-associated 5 0 0 /~ decrease in liver protein synthesis using microsomes isolated from male albino rats of ages 2-3, 7-1 I , and 19-25 months. Other workers also found a decline in protein synthesis with liver microsomes isolated from adult and senescent rats (Hrachovec, 1969;Buetow & Gandhi, 1973;Comolli, 1973;Junghahn & Bielka, 1974;Hellthaler et al, 1976;Buetow et al, 1977).…”
Section: Rationale For the Study Of Protein Metabolism During Agingmentioning
confidence: 87%
“…These results are in contradiction to a large body of literature indicating a decline in brain protein synthesis after birth. Such age-related decreases have been observed in rats (Murthy & Rappoport, 1965;Yamagami, Fritz & Rappoport, 1966;Andrews & Tata, 1971 ;Barra et al, 1973;Dunlop, Van Elden & Lajtha, 1977b), and mice (Johnson & Belytschko, 1969;Lerner & Johnson, 1970, 1971. The decreases in brain protein synthesis were reported to occur primarily during the first 3 0 days after birth (Lerner & Johnson, 1970, 1971Andrews & Tata, 1971).…”
Section: Rationale For the Study Of Protein Metabolism During Agingmentioning
confidence: 91%
See 1 more Smart Citation
“…Most studies have demonstrated an age-related decline in cell-free protein synthesis using microsomes, ribosomes, or isolated hepatocytes from rodent livers (Richardson et al, 1985;Horbach et al, 1987;Mainwaring, 1969;Hrachovec, 1971;Buetow and Ghandi, 1973;Comolli, 1973;Kurtz, 1978;Viskup et al, 1981). Several investigators have reported a marked increase in the synthesis of specific hepatic proteins, particularly albumin, during late senescence (Chen et al, 1973;van Bezooijen et al, 1976;Van Bezooijen and Knook, 1977).…”
Section: Rough-surfaced Endoplasmic Reticulummentioning
confidence: 99%
“…Age-dependent alterations in protein metabolism, especially hepatic protein synthesis, have been subjected to considerable study (for reviews, see Richardson, 1981;Richardson and Birchenall-Sparks, 1983;Richardson et al, 1985). Most studies have demonstrated an age-related decline in cell-free protein synthesis using microsomes, ribosomes, or isolated hepatocytes from rodent livers (Richardson et al, 1985;Horbach et al, 1987;Mainwaring, 1969;Hrachovec, 1971;Buetow and Ghandi, 1973;Comolli, 1973;Kurtz, 1978;Viskup et al, 1981). Several investigators have ANIMAL AGE (Months) Fig.…”
Section: Rough-surfaced Endoplasmic Reticulummentioning
confidence: 99%